Sistem Informasi Pengelolaan Persediaan berbasis Safety Stock pada Industri Konveksi Seragam Polisi - Farhan, Faris Ahmad; Setiawan, Raden Rhoedy; Irawan, Yudie (Universitas Hamzanwadi, 2025)
Manual stock management often leads to various problems, such as delayed information, recording errors, and low operational efficiency, highlighting the need for a more integrated and efficient inventory information system. This study aims to develop a web-based inventory management information system that can automatically implement the safety stock and reorder point methods. The system is designed to determine the minimum inventory level, calculate reorder timing, and provide alerts when stock reaches the minimum threshold to support more accurate restocking decisions. This is applied research that uses the Waterfall model to develop a web-based inventory system for a garment manufacturing business. The stages include needs analysis through observation and interviews, system design using flowcharts and use case diagrams, implementation using PHP and MySQL, and testing using the black-box method. Our findings resulted in an information system equipped with safety stock and reorder point features to automatically determine the minimum stock level and reorder timing. The test results showed that all features functioned properly, increasing data entry speed, improving data accuracy, and supporting better restocking decisions. This system can be used by small businesses that require efficient, real-time, and structured inventory management.